572 NUTRITIONAL PATTERNS MAY AFFECT ESOPHAGEAL ACID EXPOSURE, AND THE NUMBER AND TYPE OF GASTROESOPHAGEAL REFLUXES. (14th September 2020) - Morozov, S; Kropochev, V; Isakov, V
Abstract:  : The role of nutritional patterns on esophageal function testing parameters is not widely studied. Earlier published data focused on symptoms of GERD and their association with the food structure. Aim of the study was to assess the influence of nutritional patterns on esophageal acid exposure and types and number of gastroesophageal refluxes Methods: The data of complete examination of 165 participants served as a source data for the study. Diagnosis of GERD was based on clinical data (heartburn and acid regurgitation at least once a week for not less than 6 month, actual during last 3 month, history of effective PPI treatment), GERD-Q questionnaire (≥8 points), endoscopic evaluation (Excera II, Olympus, Japan) and 24-hours esophageal pH-impedance studies (Ohmega, MMS, the Netherlands; 2 pH, 6 impedance catheters, UnisensorAG, USA). Food frequency questionnaire was used to analyse food structure. StatSoft (USA) software was used for correlation analysis. The work has been performed within RSF 19–76-30014. Results: We enrolled 124 GERD patients and 41 controls. Significant (P < 0.05) correlation of AET was with energy value of the ration (Spearman rank R = 0.19), amount of fat (R = 0.2). Significant correlation of number of GERs was with energy values (R = 0.35), protein (R = 0.3), fat (R = 0.33), alcohol (R = 0.28) and dietary fibre (R = -0.22) consumption. Number of acid GERs correlated with calorie (R = 0.35), fat (R = 0.32), protein (R = 0.25), carbohydrates (R = 0.24) and alcohol (R = 0.24) consumption. Number of weak-acid GERs correlated with calories (R = 0.22), fat (R = 0.21), protein (R = 0.22), alcohol (R = 0.23) and dietary fibre (R = -0.24) consumption. High GERs correlated with fat (R = 0.3), protein (R = 0.22), alcohol (R = 0.25) and fibre (R = -0.25). Conclusion: High energy value, consumption of fat and alcohol showed direct medium-strength correlation with esophageal acid exposure and the total number gastroesophageal refluxes. The total number of gastroesophageal refluxes, number of weak acid and high gastroesophageal refluxes had inverse correlation with the amount of dietary fibre consumed. Found trends are used to establish nutritional patterns for reflux events in GERD patients.